Comparative effects of propofol and dexmedetomidine on cerebral hemodynamics in intracranial surgery - Rony, M. Rayhan Reza; Rahman, Mohammed Mohidur; Tannee, Tanjila Rahman; Rabiul Islam, M.; Ferdous, Jannath Ara; Rahman, Dawan Mohammad Anisur; Anwarul Mamun, M. (International Journal of Research in Medical Sciences, 2026)
Background: Maintaining stable cerebral hemodynamics is essential during intracranial surgery to ensure adequate perfusion and minimize secondary injury. This study compared the effects of propofol and dexmedetomidine on cerebral and systemic hemodynamics in patients undergoing elective intracranial surgery. Methods: In this prospective observational study, 95 adult patients were allocated into two maintenance anesthesia groups: propofol (n=48) and dexmedetomidine (n=47). Intraoperative parameters including mean arterial pressure (MAP), heart rate (HR), intracranial pressure (ICP), cerebral perfusion pressure (CPP), and regional cerebral oxygen saturation (rSO₂) were recorded at defined intervals. Brain relaxation was assessed at dural opening using a four-point scale. Postoperative recovery and complications were evaluated over 30 days. Results: Dexmedetomidine produced higher mean CPP (75.6±5.8 versus 72.3±6.5 mmHg, p=0.010), lower ICP (15.9±3.8 versus 18.1±4.7 mmHg, p=0.015), and higher rSO₂ (77.5±6.3 versus 73.2±7.1%, p=0.003) compared to Propofol. Bradycardia occurred more often with Dexmedetomidine (29.8% versus 12.5%, p=0.035), while hypotension was more frequent with Propofol (41.7% versus 25.5%, p=0.096). Dexmedetomidine was an independent predictor of good brain relaxation (OR 3.46, p=0.015), along with adequate CPP (OR 5.37, p=0.003). ROC analysis identified CPP as the best predictor of optimal brain relaxation (AUC=0.86). Conclusions: Dexmedetomidine offers superior cerebral perfusion and hemodynamic stability over propofol during intracranial surgery without increasing adverse events.